Clinical evaluation of the failure rate of metallic brackets bonded with orthodontic composites - Romano, Fábio Lourenço; Valério, Rodrigo Alexandre; Gomes-Silva, Jaciara Miranda; Ferreira, José Tarcísio Lima; Faria, Gisele [UNESP]; Borsatto, Maria Cristina (FapUNIFESP (SciELO), 2012)
The purpose of the present study was to evaluate in vivo the failure rate of metallic brackets bonded with two orthodontic composites. Nineteen patients with ages ranging from 10.5 to 38.7 years needing corrective orthodontic treatment were selected for study. The enamel surfaces from second premolars to second premolars were treated with Transbond Plus-Self Etching Primer (3M Unitek). Next, 380 orthodontic brackets were bonded on maxillary and mandibular teeth, as follows: 190 with Transbond XT composite (3M Unitek) (control) and 190 with Transbond Plus Color Change (3M Unitek) (experimental) in contralateral quadrants. The bonded brackets were light cured for 40 s, and initial alignment archwires were inserted. Bond failure rates were recorded over a six-month period. At the end of the evaluation, six bond failures occurred, three for each composite. Kaplan-Meyer method and log-rank test (Mantel-Cox) was used for statistical analysis, and no statistically significant difference was found between the materials (p=0.999). Both Transbond XT and Transbond Plus Color Change composites had low debonding rates over the study period.
Keywords: Debonding; Orthodontic brackets; Orthodontics